The Security Dilemma and Arms Race Dynamics in Europe’s Response to the Russia-Ukraine Conflict - Lee, Brice Tseen Fu; Komšić, Filip; Sims, Juan Pablo (Journal of Strategic and Global Studies, 2024)
This paper examines the escalation of military expenditures in Europe in response to the ongoing Russia-Ukraine conflict, through the lens of the security dilemma. The security dilemma, a fundamental concept in international relations, describes how the defensive actions of one state can provoke perceptions of threat among others, potentially leading to an arms race. By analyzing military spending data from 2019 to 2023 for key European countries including Estonia, Latvia, Poland, Azerbaijan, Russia, Finland, France, Germany, Italy, and the United Kingdom, both in absolute terms and as a percentage of GDP, this study highlights how nations closest to the conflict, such as Poland and the Baltic states (Estonia and Latvia), have significantly increased their defense budgets in reaction to perceived immediate threats. These increases are mirrored, albeit to a lesser extent, by major Western European powers and other countries in the region, reflecting a continent-wide trend in military buildup. The findings suggest that while these increases are primarily defensive in nature, they carry the risk of being misinterpreted as offensive postures by neighboring countries, thereby exacerbating the security dilemma. This paper argues for the necessity of enhanced diplomatic efforts to mitigate these risks. It advocates for the establishment of mechanisms that foster clear dialogue and mutual understanding to ensure that military enhancements contribute positively to regional stability rather than escalating tensions. Through the security dilemma, this study contributes to a deeper understanding of how European nations can navigate the complexities of increased military spending and regional security in turbulent times.